A new species of Holotachysphex de Beaumont, 1940 (Hymenoptera, Apoidea, Crabronidae) from Iran with identification key to species - Schmid-Egger, Christian; Fallahzadeh, Majid; Khosroabadi, Mahdi; Ljubomirov, Toshko (Zootaxa, 2016)
Holotachysphex iraniensis sp. nov. (Hymenoptera, Apoidea, Crabronidae) from southern Iran is described. A revised key to the world species of Holotachysphex is provided. A red form of H. mochii from Jordan is described.